Autophagy and skin diseases: a review - Ghada M El-Hanafy; Hanan R Nada; Marwa F Mousa; Maha F Elmasry (Journal of the Egyptian Women’s Dermatologic Society, 2021)
Autophagy is an evolutionary maintained, extremely controlled lysosomal degradation process for cellular components, which is necessary for cellular homeostasis, viability, and maintenance. The authors aimed through this review to emphasize the crucial role of autophagy in different diseases, particularly in various skin diseases. The authors conclude from this review that the disturbance of the autophagy process could be an important etiopathogenic factor in many cutaneous disorders. This could open a new era in the understanding of the etiology of such diseases and, hence, their treatment.